2012
DOI: 10.1111/j.1750-2659.2012.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations from pandemic Influenza [A(H1N1)pdm09] infections among type 1 and 2 diabetes patients in Spain

Abstract: Objectives  To describe and analyze the clinical characteristics and outcomes for all patients with diabetes who were hospitalized with laboratory‐confirmed A(H1N1)pdm09 infections in Spain during 2009. Methods  Observational retrospective study using data collected by the Spanish National Hospital Discharge Database. We selected all admissions with diagnosis ICD‐9‐CM code 488·1 [A(H1N1)pdm09]. Discharges were grouped as follows: no diabetes, Type1 and Type 2 diabetes. Underlying medical conditions and risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Moreover, since over one-third of diabetes is undiagnosed in the community [48], the lack of a population control group in case series of pH1N1 hospitalisations makes it difficult to ascertain whether the apparent effect of diabetes on pH1N1 hospitalisations is due to increased detection of diabetes in tertiary care. The prevalence of diabetes in pH1N1 patients may be consistent with its community prevalence if undiagnosed diabetes is included [46]. To our knowledge, our study is one of only two studies [12] to have identified and followed individuals, in the general population, with and without diabetes, for influenzaattributable outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, since over one-third of diabetes is undiagnosed in the community [48], the lack of a population control group in case series of pH1N1 hospitalisations makes it difficult to ascertain whether the apparent effect of diabetes on pH1N1 hospitalisations is due to increased detection of diabetes in tertiary care. The prevalence of diabetes in pH1N1 patients may be consistent with its community prevalence if undiagnosed diabetes is included [46]. To our knowledge, our study is one of only two studies [12] to have identified and followed individuals, in the general population, with and without diabetes, for influenzaattributable outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Diabetes appears disproportionately represented in most studies of confirmed pH1N1 cases requiring hospitalisation [36,[42][43][44][45]. Some pH1N1 studies have also identified diabetes as a risk factor for severe outcomes following hospitalisation [45], although other studies have not [46,47]. Whether the high prevalence of diabetes in pH1N1 studies can be attributed to a diabetes-effect on risk [45], confounding due to other comorbidities [46,47] or due to adults with diabetes being more readily admitted on a precautionary basis [35] remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first year of the pandemic, infections resulted in >100 000 deaths worldwide [2][3][4]. Increased lethality was particularly observed in patients with diabetes and obesity, but also in pregnant women [5][6][7]. The majority of infections, however, had a less severe course of disease [8].…”
mentioning
confidence: 99%
“…It needs to be considered that diabetes, is among the comorbidities involved in a severe outcome of influenza virus infection and it triples the risk of hospitalization after influenza A(H1N1)pdm09 infection (Jimenez-Garcia et al, 2013). However, the results of multivariate analysis have suggested that possibly concomitant conditions such as obesity, frequently found among diabetic persons, highly increases the risk of very severe infection or even death, and not only diabetes itself (Jimenez-Garcia et al, 2013). The patient from whom A/Aragón/270/2014 virus was isolated did not have obesity and his levels of glycated hemoglobin were within the levels of the control population indicating a good control of blood glucose levels upon infection.…”
Section: Discussionmentioning
confidence: 99%